Aesthetic mobile learning interfaces ranking based on TOPSIS approach / Nor Fatin Farzana Zainuddin ... [et al.] - Zainuddin, Nor Fatin Farzana; Abu Bakar, Zuriana; Mohammad, Noor Maizura; Mohamed, Rosmayati (Faculty of Information Management, 2022)
The Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) approach is applied to evaluate the aesthetic of mobile learning interfaces. TOPSIS approach is a valuable distance-based technique for ranking and selecting several alternatives. Nine design principles, balance, proportion, simplicity, and others, are applied in mobile learning interface design. There are 15 mobile learning interfaces divided into three types of interfaces, namely Homepage, Introduction page, and Learning page. This study found that Interface 1 (Homepage), Interface 6 (Introduction Page), and Interface 15 (Learning Page) are the interfaces that are considered aesthetic for mobile learning interfaces.